Dynamic Hydrogen‐Bond Network as a Modulator of Bismuth–Antimony Complex Anodes for Self‐Healable and Wider Temperature Adaptive Potassium Ion Batteries. (4th April 2023) - Liu, Yihui; Liu, Fusheng; Liu, Bingbing; Xiao, Yaoyao; Qin, Guohui; Ma, Jianmin
Abstract: Antimony (Sb)‐based anodes are attractive candidates in potassium‐ion batteries (PIBs) due to their superior capacities and rational potassium inserting voltages. However, the sluggish kinetics and poor interface compatibility severely hinder practical application. Herein, Bi0.67 Sb1.33 S3 nanospheres embedded into in situ formed poly(3, 4‐ethylenedioxythiophene) crosslinked with polythioctic acid (PET@PTA) (Bi0.67 Sb1.33 S3 /PET@PTA) were elaborately conceptualized with hydrogen bonds exchangeable binding (HBEB) sites. Bi0.67 Sb1.33 S3 /PET@PTA exhibits notable self‐healing ability and wider temperature adaptability. Bi0.67 Sb1.33 S3 /PET@PTA displays an impressive capacity of 819 mAh g −1 at 0.05 A g −1, prominent cycle ability with a 73 % capacity conservation after 500 cycles at 2 A g −1, and high capacity retention of 66 % and 84 % at −40 and 70 °C to that case at room temperature, respectively, for potassium storage. This work provides a new perspective for HBEB sites in maximizing the desirable K + storage performance. Abstract : Bi0.67 Sb1.33 S3 nanoparticles deposited on poly(3, 4‐ethylenedioxythiophene) (PET) are confined when the polymer is crosslinked with polythioctic acid (PTA) (Bi0.67 Sb1.33 S3 /PET@PTA). This material exhibits wider temperature adaptability for potassium storage, benefiting from a greater number of hydrogen bonds exchangeable binding (HBEB) sites. Moreover, in‐depth insights into the intrinsic formation and potassium‐storage mechanisms are also put forward.